2017
DOI: 10.1111/anec.12483
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of 38 heart rate variability measures to the addition of artifact in human and artificial 24‐hr cardiac recordings

Abstract: Short-term time domain HRV measures are more sensitive to added artifact than long-term measures. Absolute power frequency domain measures across all frequency bands are more sensitive than normalized and relative frequency domain measures. Most nonlinear HRV measures assessed were relatively robust to added artifact, with Poincare plot SD1 being most sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…Although previous studies have shown a possible correlation between the different measures [ 33 , 34 ], an exact equivalence has not been reported. It is possible that Poincaré plots may detect abnormalities that are not as easily detectable with traditional time-domain measures, given that each parameter has different sensitivity to noise and other experimental conditions [ 35 ]. Hence, further investigations to fully uncover and understand the physiological relevance of these autonomic assessment methods are warranted in order to determine the efficacy of the different metrics in accurately quantifying autonomic activity”.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown a possible correlation between the different measures [ 33 , 34 ], an exact equivalence has not been reported. It is possible that Poincaré plots may detect abnormalities that are not as easily detectable with traditional time-domain measures, given that each parameter has different sensitivity to noise and other experimental conditions [ 35 ]. Hence, further investigations to fully uncover and understand the physiological relevance of these autonomic assessment methods are warranted in order to determine the efficacy of the different metrics in accurately quantifying autonomic activity”.…”
Section: Discussionmentioning
confidence: 99%
“…They primarily respond to the body's regulatory functions and are hypersensitive to noise from movement, changes in breathing rate and speech (Jorna, 1992;Young, 2000). We recorded heart activity and explored LF/HF ratio and standard deviation of inter-beat intervals, as they are related to mental workload and less affected by artifacts than other variability measures (Stapelberg, Neumann, Shum, McConnell, & Hamilton-Craig, 2017). Eye measures related to workload include blink rate, horizontal gaze dispersion (for highway driving) and pupil diameter (Marquart, Cabrall, & de Winter, 2015).…”
Section: Measuring Workloadmentioning
confidence: 99%
“…Several studies have reported the importance of artefact correction on the quantification of HRV derived parameters from short-term recordings [8,28,29]. However, there is scarce evidence regarding the impact of using different Kubios filters on the quantification of HRV derived parameters from short-term recordings in time-and frequency-domains employing the commercially available Kubios software [10].…”
Section: Discussionmentioning
confidence: 99%
“…HRV recordings using heart rate monitors are affected by technical (e.g., wrong placement of the heart rate monitor's band) and/or biological (e.g., ectopic beats) artefacts. These artefacts could contaminate the HRV recordings, making it difficult to obtain HRV derived parameters from long-term (≈24 h) and especially short-term (≈5 min) recordings [1,7,8]. Artefacts could modify and produce important over-or under-estimation of HRV derived parameters (up to 50%) [9].…”
Section: Introductionmentioning
confidence: 99%